Grupy interesu. Dwie perspektywy - Tkocz, Zygmunt (Interest group. Two perspectives, 2006)
This is tentative approach to certain problems of sociological theory. Many sociologists have for several years considered it necessary to discuss a number of issues connected with the structure and evolution of contemporary societies. The author of the article discusses the problem of interest groups in the USA, Western Europe - on the national level - and some attributes of interest group in the European Union. It is the initial link in the long and complicated process of the formation of political and economic decisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 37-48